Influence of radial versus femoral access site on coronary angiography and intervention outcomes: A systematic review and meta‐analysis. Issue 7 (25th May 2017) - Brener, Michael I.; Bush, Aaron; Miller, Julie M.; Hasan, Rani K.
Abstract : Objectives: Systematic review and meta‐analysis of randomized clinical trials (RCT) to compare procedural outcomes between radial access (RA) and femoral access (FA). Background: Recent RCTs suggest RA for coronary angiography and percutaneous coronary intervention reduces bleeding complications, but controversy exists regarding other benefits and risks relative to FA. Methods: Searches of MEDLINE, EMBASE, CENTRAL, LILACS, and major conference abstracts identified relevant studies published from 1985‐2016. We qualitatively evaluated study methodology and risk of bias. Quantitative data were abstracted relevant to the primary endpoints of major adverse cardiovascular events (MACE) and major bleeding (MB), and secondary outcomes including vascular complications and procedural failure. Results: We identified 2, 098 titles, from which 48 studies with 29, 446 patients met inclusion criteria for our analysis. We found there was a significant reduction of MACE with RA versus FA (RR 0.86, 95% CI 0.77–0.95, I 2 = 0%), driven by a reduction in death, but not MI or stroke. MB occurred less frequently with RA (RR 0.54, 95% CI 0.44–0.67, I 2 = 4%). Vascular complications were also reduced with RA (RR 0.39, 95% CI 0.25–0.59, I 2 = 75%), while procedural failure was more common (RR 2.15, 95% CI 1.65–2.82, I 2 = 53%), although there was significant statistical heterogeneity for both of these outcomes. Most studies demonstrated low risk of selection and attrition biases, but high risk of detection bias. Conclusions: Radial access reduces the risk of death, major bleeding, and vascular complications as compared to femoral access but increases the risk of procedural failure. © 2017 Wiley Periodicals, Inc.